3T3-L1 preadipocytes exhibit heightened monocyte-chemoattractant protein-1 response to acute fatty acid exposure. - Aimee L Dordevic (Public Library of Science (PLoS), 2014)
Preadipocytes contribute to the inflammatory responses within adipose tissue. Whilst fatty acids are known to elicit an inflammatory response within adipose tissue, the relative contribution of preadipocytes and mature adipocytes to this is yet to be determined. We aimed to examine the actions of common dietary fatty acids on the acute inflammatory and adipokine response in 3T3-L1 preadipocytes and differentiated mature adipocytes. Gene expression levels of key adipokines in 3T3-L1 preadipocytes and adipocytes were determined following incubation with palmitic acid, myristic acid or oleic acid and positive inflammatory control, lipopolysaccharide for 2 and 4 h. Inflammatory kinase signalling was assessed by analysis of nuclear factor-κB, p38-mitogen-activated protein kinase and c-jun amino-terminal kinase phosphorylation. Under basal conditions, intracellular monocyte chemoattractant protein-1 and interleukin-6 gene expression levels were increased in preadipocytes, whereas mature adipocytes expressed increased gene expression levels of leptin and adiponectin. Fatty acid exposure at 2 and 4 h increased both monocyte chemoattractant protein-1 and interleukin-6 gene expression levels in preadipocytes to greater levels than in mature adipocytes. There was an accompanying increase of inhibitor of κB-α degradation and nuclear factor-κB (p65) (Ser536) phosphorylation with fatty acid exposure in the preadipocytes only. The current study points to preadipocytes rather than the adipocytes as the contributors to both immune cell recruitment and inflammatory adipokine secretion with acute increases in fatty acids.